Modeling Newspaper Distribution as Capacitated Vehicle Routing Problem with Time Window: Case Study of Daily Graphic Newspaper, Ashanti Region, Ghana - , Wallace Agyei, Kwaku Fokuoh Darkwah, William Obeng-Denteh, Emmanuel Appoh Andam (Archives of Current Research International, 2015)
The distribution problem of Daily Graphic newspaper in Ashanti region, Ghana is discussed in this paper. The problem was modelled as Capacitated Vehicle Routing Problem with Time Window (CVRPTW) and the Clark and Wright’s Savings with local search algorithm was used to solve the problem. The algorithm takes the travel time matrix as input and proceeds to find the travel time savings between all the district capitals. The proposed algorithm was integrated into VRP heuristic program. Comparison of results in terms of the total traveling time obtained by the Clarke and Wright savings with local search algorithm and the current manual routes maintained by company indicated that the current total travelling time can be reduced by up to 21.9%.